Second-generation extracellular matrix patch for epicardial infarct repair - Bhatt, Arjun; Bates, Michael J.; Marcu, Constantin; Carabello, Blase A.; Yin, Kanhua; Boyd, Walter Douglas (My University, 2023)
Current myocardial infarction treatments focus on improving hemodynamics rather than addressing the problem of lost myocardium impairing left ventricular function. Epicardial infarct repair with a bioactive patch placed on the ischemic area is an emerging approach to promote endogenous myocardial repair. We report the use of a second-generation CorMatrix-extracellular matrix (ECM) patch as an adjunct to surgical revascularization in treating a young patient with diffuse, multivessel coronary artery disease unamenable to PCI and a large anterior myocardial infarction. The progressive myocardial scar shrinkage and increase in left ventricular ejection fraction from 10 to 51% are generally not observed with surgical revascularization therapy alone, suggesting this new patch has adjunctive potential to current revascularization therapy.
Keywords: Myocardial infarction; Ischemic heart disease; Extracellular matrix patch; Myocardial scar